2013
DOI: 10.1152/ajprenal.00574.2012
|View full text |Cite
|
Sign up to set email alerts
|

Effects of urethane on reflex activity of lower urinary tract in decerebrate unanesthetized rats

Abstract: Effects of urethane on lower urinary tract function were examined in decerebrate unanesthetized rats. During single slow infusion (0.04 ml/min) cystometrograms (CMGs), urethane (0.3 g/kg) increased micturition pressure threshold (PT) by 73%, postvoid residual volume (RV) by 425%, and decreased voiding efficiency (VE) by 57%, but did not change maximal voiding pressure (MVP), closing peak pressure (CPP), bladder compliance, bladder contraction duration (BCD), or volume threshold (VT) for inducing micturition. L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
32
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 20 publications
(40 reference statements)
3
32
1
Order By: Relevance
“…This suggests that in the former mice, the awake forebrain was the site likely responsible for the decreased volume threshold, since it has an excitatory input as well as an inhibitory input into the brain stem, which contains the switching mechanism for micturition initiation (11). In general, neurally intact conscious mice under normal circumstances are known to have a larger bladder capacity than decerebrate (unanesthetized) mice (42,49).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that in the former mice, the awake forebrain was the site likely responsible for the decreased volume threshold, since it has an excitatory input as well as an inhibitory input into the brain stem, which contains the switching mechanism for micturition initiation (11). In general, neurally intact conscious mice under normal circumstances are known to have a larger bladder capacity than decerebrate (unanesthetized) mice (42,49).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a recent study by Sorge et al (33) revealed that the pain response in conscious rodents is remarkably influenced by olfactory stimuli from male experimenters, strongly suggesting that data analysis would be confounded when in vivo experiments are performed in awake animals. On the other hand, anesthetics are known to interfere with both reflex micturition (23,49) and the pharmacological effects of drugs such as glutamatergic antagonists (47,48,50). As an alternative, animals under decerebrate unanesthetized conditions whose forebrains were previously removed under inhalation anesthesia can be used to examine reflex responses during cystometry (43,45).…”
mentioning
confidence: 99%
“…(Yoshiyama et al, 2013) and placed in a restraining cage (KN-326, Natsume). The bladder catheter was connected to a pressure transducer (Transbridge, WPI) and a microinjection pump (SP2001, WPI).…”
Section: Methodsmentioning
confidence: 99%
“…However, these cystometric VVs are remarkably small compared with mouse spontaneous VVs estimated from voided spots on paper (ranging from 200 to 520 l) (12,16,22). It has been suggested that the low VV as measured by mouse cystometry can be attributed to the inhibition of bladder function caused by anesthesia (25), laparotomy, and bladder catheter placement. Because bladder catheter placement will affect bladder wall movement in cystometry, the catheter position in the mouse bladder is one of the most important factors.…”
mentioning
confidence: 94%